Molecular Characterizations of Double-Stranded RNA Degrading Nuclease Genes from Ostrinia nubilalis - Anastasia M. W. Cooper; Huifang Song; Xuekai Shi; Zhitao Yu; Marcé Lorenzen; Kristopher Silver; Jianzhen Zhang; Kun Yan Zhu (Insects, 2020)
Variable RNA interference (RNAi) efficiencies limit RNAi-based pest management strategies for many pests. Previous efforts to understand mechanisms contributing to low RNAi efficiency indicate that double-stranded RNA (dsRNA) is degraded in the European corn borer (ECB), Ostrinia nubilalis, due to nuclease activity. To investigate the contribution of dsRNA-degrading endonucleases (dsRNases) and lepidopteran-specific RNAi efficiency-related nucleases (REases) to dsRNA instability and low RNAi efficiency in ECB, five complementary DNAs putatively encoding four dsRNases (OndsRNase1, 2, 3, and 4) and one REase (OnREase) were sequenced. Characterization of these transcripts revealed that substrate specificity might vary among the four dsRNases due to different amino acid combinations in the substrate-binding sites. Gene expression analysis indicated that OndsRNase2 and OnREase were highly expressed in the larval gut, and OndsRNase1 showed the highest expression in hemolymph, especially in older developmental stages. Transcript level analysis after dsRNA exposure revealed that expression of OnREase rapidly increased upon dsRNA ingestion or injection, whereas OndsRNase4 expression only increased after long-term ingestion of dsRNA. While the biological function of these nucleases remains to be verified, our results suggest that OnREase and OndsRNase2, and OndsRNase1 and OndsRNase4 may be responsible for degradation of dsRNAs in the ECB gut and hemolymph, respectively, thereby contributing to low RNAi efficiency.